DESIGN OF FILTERED LOW NOISE AMPLIFIER BASED ON SUBSTRATE INTEGRATED WAVEGUIDE AND BIPOLAR JUNCTION TRANSISTOR - Rahayu, Novelita
In wireless communication, the demand for more compact radio frequency (RF) receiver applications, relatively low production costs, and excellent performance is a vital necessity. A number of studies were done to meet these requirements. Optimizing the performance of RF receivers focuses mostly on integrating several RF receiver system components through research. This study discusses the design, simulation, and implementation of an integrated low noise amplifier (LNA) filter. The filtered low noise amplifier (FLNA) arrangement comprises of an integrated transistor-based LNA and a bandpass filter (BPF) produced using the substrate integrated waveguide (SIW) technique. The suggested FLNA, which is meant to operate at a center frequency of 2.4 GHz, is designed and fabricated on a flame retardant (FR) 4 epoxy dielectric substrate of 1.6 mm in thickness. According to the results of the characterization, the realized FLNA has a -3 dB bandwidth of 980 MHz (1.88 GHz–2.86 GHz) and a gain of 11.012 dB. These results are comparable to the simulated outcomes, proving the RF's appropriateness.